KREASI SAYUR BAYAM MENJADI MASKER WASEBAGAI POTENSI DAERAH MELALUI EKONOMI KREATIF DI KELURAHAN BONTO LEBANG KABUPATEN TAKALAR SULAWESI SELATAN - Siti Aisyah (LP2M STP Mataram, 2021)
The creative economy industry is predicted to become a future industry as a fourth wave industry, which emphasizes creative ideas and ideas. The potential of the creative industry in the creative economy sector in the future will remain an important alternative in increasing contributions in the economic and business fields, improving the quality of people's lives, communication media, fostering innovation and creativity, and strengthening the identity of a region (city branding). This Community Service aims to increase knowledge about spinach cultivation and the creation of spinach vegetables into facial masks. In the implementation of this service, this service is carried out with counseling on how to process facial masks made from the basic ingredients of spinach vegetables. This Community Service is located in Bontolebang Village, located in the capital city of the District and has its own meaning consisting of the words Bonto and Lebang, namely Bonto which means Altitude and Lebang which means Place for Discussion, so Bonto Lebang means a high place which is used as a place for deliberation by the community